Independence of the National Police Commission According to Presidential Regulation No. 17 of 2005 - M Arief Bona A; Syaifuddin (Journal of Law Science, 2022)
The purpose of this study is to determine the implementation of the duties and functions of the police commission according to Presidential Regulation No. 17 of 2005 concerning the National Police Commission, to determine the independence of the National Police Commission, to determine the factors that support or hinder the independence of the Police Commission. The approach used is a normative and sociological juridical approach. The normative juridical approach is the process of analyzing the problem from the point of view/according to the applicable laws/statutory provisions. The sociological approach, namely by looking at aspects of social dynamics that are developing and always changing in society, and in the administration of the state. Kompolnas independence is not mentioned in writing in Law Number 2 of 2002 concerning the Indonesian National Police and Presidential Regulation Number 17 of 2005 concerning Kompolnas, however when viewed from hierarchical relationships, recruitment patterns, performance and accountability, Kompolnas is still relevant for referred to as an independent institution in carrying out its duties and functions. Various factors that support the independence of Kompolnas such as the Organizational Principles and Kompolnas Regulations, the composition of Kompolnas members and also the Kompolnas decision-making system further strengthen the independence of Kompolnas which can then cover for weaknesses which become factors inhibiting Kompolnas independence such as Normative Factors, Appointment and Dismissal of Kompolnas members, and Kompolnas Secretariat.